Klasifikasi Pemain Futsal Menggunakan Metode Simple Multi Attributte Rating Technique (SMART) - Agus Budhi Marendra; Didik Nugroho; Iwan Ady Prabowo (STMIK Sinar Nusantara, 2018)
The development of futsal sports is currently very rapid. This can be seen from the many futsal clubs that have sprung up with very many members with the same average ability, making it difficult for a coach to determine the first team in the club. One of the uses of information technology is the use of a player's classification system for determining the main team in a futsal club. The method used to classify futsal players is a simple multi-attribute algorithm rating technique is chosen because this method can solve with many criteria or multi attributes besides that in this method also has a direct weighting technique that is more flexible because the user can change the criteria weight according to the level the desired interest, and this method will be applied to determine the players who registered in the recruitment of players who will enter the team and determine the core and reserve teams that will be brought to a competition. The data used in testing this system amounted to 30 player data obtained from the club's routine training. The results of manual data calculations with system calculations using the Simple Multi-Attribute Rating Technique (SMART) algorithm are the same results.Keywords: Futsal, Recruitment, Simple Multi-Attribute Rating Technique (SMART)